2009
DOI: 10.1016/j.brainres.2009.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and ultrastructural features of Iba1-immunolabeled microglial cells in the hippocampal dentate gyrus

Abstract: Microglia are found throughout the central nervous system, respond rapidly to pathology and are involved in several components of the neuroinflammatory response. Iba1 is a marker for microglial cells and previous immunocytochemical studies have utilized this and other microglial-specific antibodies to demonstrate the morphological features of microglial cells at the light microscopic level. However, there is a paucity of studies that have used microglial-specific antibodies to describe the ultrastructural feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 31 publications
8
65
0
1
Order By: Relevance
“…The observed changes in morphology of glia, from the “quiescent” phenotype in naïve mice to the “reactive” phenotype in treated mice, were consistent with the activated state of glia (Shapiro et al, 2009). The majority of the Iba1-positive cells in the dorsal horn that displayed this changed morphology also expressed the activated form of p38 MAP kinase and the GFAP-positive cells expressed the activated form of c-Jun-Activated Kinase (JNK), as revealed by a double immunofluorescence using phospho-specific antibodies (Han, Willcockson and Valtschanoff, unpublished observations), providing independent evidence for activation of microglia (Ji and Suter, 2007; Tsuda et al, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…The observed changes in morphology of glia, from the “quiescent” phenotype in naïve mice to the “reactive” phenotype in treated mice, were consistent with the activated state of glia (Shapiro et al, 2009). The majority of the Iba1-positive cells in the dorsal horn that displayed this changed morphology also expressed the activated form of p38 MAP kinase and the GFAP-positive cells expressed the activated form of c-Jun-Activated Kinase (JNK), as revealed by a double immunofluorescence using phospho-specific antibodies (Han, Willcockson and Valtschanoff, unpublished observations), providing independent evidence for activation of microglia (Ji and Suter, 2007; Tsuda et al, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…Building on previous EM observations that microglia contact axon terminals and dendritic spines [9],[44],[45], our quantitative analysis revealed that most microglial processes directly appose not only axon terminals and dendritic spines, but also perisynaptic astrocytic processes and synaptic clefts. Our SSEM with 3-D reconstructions also uncovered the 3-D relationships between microglia and synapses, revealing that microglial processes contact multiple synapse-associated elements at multiple synapses simultaneously.…”
Section: Discussionmentioning
confidence: 53%
“…As IbaI is commonly used for morphometric and ultrastructural analyses of microglia (Shapiro et al ., 2009), we performed the same morphological analysis in brain sections immunolabeled with anti-IbaI (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%